Traveloka Digital Marketing Strategy Analysis Through Instagram: Analisis Strategi Digital Marketing Traveloka Melalui Instagram - Agustin, Tri Putri; Febriana, Poppy (Indonesian Journal of Innovation Studies, 2023)
With the advent of the internet, the development of marketing to a new level, marketing through the internet is called digital marketing. This study discusses the digital marketing strategy carried out by Traveloka. Traveloka is an online ticket reservation service company that has succeeded in gaining sales. This study aims to explain how Traveloka's digital marketing strategy analysis is centered on Instagram social media. In this study, the author uses a qualitative descriptive paradigm. As well as making observations on Traveloka's Instagram social media to support the writing of this final project. The author uses the method of analysis of the Marketing Mix Marketing Mix Booms and Bitner, 1981. (Product, Price, Place, Promotion, People, Physical Evidence, process). Based on the results of Traveloka's research, it involves the role of Digital Marketing in almost all marketing and sales activities. The use of digital media really helps Traveloka in carrying out its marketing functions efficiently and effectively.